Aircraft NCAR C-130 Documentation and Data Quality Materials (Link to NCAR/RAF) [NCAR/RAF] (Arctic Data Center, 2016)
The SHEBA C-130 dataset documentation (most of the materials made available in the previously-released data notebooks) have been put on-line via the RAF Web site. This will enable all users of the data to access the most critical documentation and data quality materials and to assemble their own copies of the documentation package.